Blockchain and 6G: the future of secure and ubiquitous communication - Khan, Ali Hussain (2022)
Future communication will be characterized by ubiquitous connectivity and security. These features will be essential requirements for the efficient functioning of futuristic applications. In this article, in order to highlight the impact of blockchain and 6G on future communication systems, we categorize these application requirements into two broad groups. In the first category, called Requirement Group I (RG-I), we include the performance-related needs on data rates, latency, reliability and massive connectivity, while in the second category, called Requirement Group II (RG-II), we include the security-related needs on data integrity, non-repudiability, and auditability. With blockchain and 6G, network decentralization and resource sharing would minimize resource under-utilization, thereby facilitating RG-I targets. Furthermore, through appropriate selection of blockchain type and consensus algorithms, RG-II needs of 6G applications can also be readily addressed. Through this study, the combination of blockchain and 6G emerges as an elegant solution for secure and ubiquitous future communication.